ANALISIS PENGELOLAAN AIR BERSIH BERBASIS MASYARAKAT DI DESA BORO-BORO LAMEURU KECAMATAN RANOMEETO BARATKABUPATEN KONAWE SELATAN - Intan Purnama Sari, Misna; Ihsan Mattalitti, Muhammad; Awalludin Ma'ruf, Andi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Kendari, 2021)
This research uses a qualitative approach, data collection is carried out throughobservation, interview techniques, documents, or literature study. The informants in thisstudy were collected in Boro-Boro Lameuru Village, Clean Water Manager, PAB Treasurer,3 Implementing Units, then the community or 4 customers and Co-Facilitators. The resultsof the study found that clean water in the area is managed in an organized manner byapplying management principles, starting from the planning stage, to communityinvolvement in the use and maintenance of clean water management facilities andinfrastructure. Clean water management has involved the village government andcommunity so that the organization and management of clean water management areformed. All program activities have been well planned in an organizational forum, namelyClean Water Management in Boro-Boro Lameuru Village. The technical implementation oroperation of this PAB is to distribute clean water to the community or customers from aclean water source, namely the Boro-Boro river. The system for withdrawing fees ormembership fees is carried out every month. The withdrawal of fees or levies is based onthe results of member meetings and is known by the local Village Head. and outlined invillage regulations. This program involves community participation in the use of cleanwater management, care, and maintenance, as well as the extent to which community-based clean water management is implemented and services.